A study on the strengthening process of world top-level womentable tennis choppers - Nonaka, Y.; Ando, S.; Yamada, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The purpose of this research was to clarify the "technical training" activity actually employed by table tennis players, targeting world`s top-level women choppers. A survey was conducted using a semi-structured interview based on qualitative research focusing on the process by which players strengthened their skill. The subjects were 7 women choppers who were ranked within the world top 50 by the International Table Tennis Federation in February 2017. The results indicated that all of them had gone through a process in which, after they had become choppers, they made efforts to acquire "cut and push" skill at the first stage, after which there was a period of transformation in their style of play to one of attack. Finally, they made efforts to explore original playing techniques by confronting problems with their individual style. With regard to their current approach to individual problems, the following aspects were emphasized: 1. The importance of the early stage of a rally, from the serve to the 3rd or 4th ball; 2. The importance of a long rally, i.e. being able to hold out tenaciously; 3. The importance of an attack technique without a fixed idea, which is an approach hardly adopted by choppers; and 4. A playing style that considers players` tasks and aptitudes, to make full use of reflections from games. Clarification of the overall picture of the strengthening process of top players may make it possible to devise individual training concepts by imaging their futures, suggesting the need to propose a new training activity.